2021
DOI: 10.1111/ajr.12821
|View full text |Cite
|
Sign up to set email alerts
|

Role of psychological distress on long‐term risky and heavy‐episodic drinking patterns in major cities and rural and remote areas

Abstract: Objective: Psychological distress and alcohol consumption are associated but few studies have focused on the association with problematic drinking in semiurban and rural settings. In this study, we assessed the role of psychological distress on various measures of problematic drinking in urban, semi-urban and rural settings. Design: Retrospective descriptive study Setting Setting: National Drug Strategy Household Survey population health survey data Participants: 151,341 Australian residents Main outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although dual diagnosis is a condition that incorporates two major public health issues, its understanding is lacking and is generally only studied in United States population groups [ 20 , 21 ]. In our study, we reported that psychological distress had a significant impact on increased risk for problematic alcohol use in females only [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although dual diagnosis is a condition that incorporates two major public health issues, its understanding is lacking and is generally only studied in United States population groups [ 20 , 21 ]. In our study, we reported that psychological distress had a significant impact on increased risk for problematic alcohol use in females only [ 22 ].…”
Section: Introductionmentioning
confidence: 99%